Comprehensive identification of conditionally essential genes in mycobacteria - Sassetti, Christopher M. (The National Academy of Sciences, 2001)
An increasing number of microbial genomes have been completely sequenced, and the identified genes are categorized based on their homology to genes of known function. However, the function of a large number of genes cannot be determined on this basis alone. Here, we describe a technique, transposon site hybridization (TraSH), which allows rapid functional characterization by identifying the complete set of genes required for growth under different conditions. TraSH combines high-density insertional mutagenesis with microarray mapping of pools of mutants. We have made large pools of independent transposon mutants in mycobacteria by using a mariner-based transposon and efficient phage transduction. By using TraSH, we have defined the set of genes required for growth of Mycobacterium bovis bacillus Calmette–Guérin on minimal but not rich medium. Genes of both known and unknown functions were identified. Of the genes with known functions, nearly all were involved in amino acid biosynthesis. TraSH is a powerful method for categorizing gene function that should be applicable to a variety of microorganisms.